The de novo synthesis of ubiquitin: Identification of deubiquitinases acting on ubiquitin precursors - Grou, CP (2015)
Protein ubiquitination, a major post-translational modification in eukaryotes, requires an adequate pool of free ubiquitin. Cells maintain this pool by two pathways, both involving deubiquitinases (DUBs): recycling of ubiquitin from ubiquitin conjugates and processing of ubiquitin precursors synthesized de novo. Although many advances have been made in recent years regarding ubiquitin recycling, our knowledge on ubiquitin precursor processing is still limited, and questions such as when are these precursors processed and which DUBs are involved remain largely unanswered. Here we provide data suggesting that two of the four mammalian ubiquitin precursors, UBA < inf > 52 < /inf > and UBA < inf > 80 < /inf > , are processed mostly post-translationally whereas the other two, UBB and UBC, probably undergo a combination of co-and post-translational processing. Using an unbiased biochemical approach we found that UCHL < inf > 3 < /inf > , USP < inf > 9 < /inf > X, USP < inf > 7 < /inf > , USP < inf > 5 < /inf > and Otulin/Gumby/FAM < inf > 105 < /inf > b are by far the most active DUBs acting on these precursors. The identification of these DUBs together with their properties suggests that each ubiquitin precursor can be processed in at least two different manners, explaining the robustness of the ubiquitin de novo synthesis pathway.